(untitled) (Global Journal of Human-Social Science, 2014)
Capabilities and facilities in urban areas have developed through the past of several years. The appearance of these capabilities and facilities has come out through the cost of financial, human and environmental. Mere attention to physical, skeletal and population and ignorance social factors in many of the previous studies has caused the failure of them. The purpose of the present study is assessment of the social capacity of Dehdasht city quarters. The method of the study is analytical-scale and has been conducted according to documentary and library research.